First-Time International Bond Issuance-New Opportunities and Emerging Risks - Guscina, Anastasia (IMF Working Papers; Working Paper ;, 2014)
International bond issuance by debut issuers has risen in recent years. The uptick was a result of both demand and supply factors. The search for yield and demand for portfolio diversification have resulted in demand-driven easy financing conditions. At the same time, rising financing needs for many debut issuers, coupled with reduced access to concessional financing, relatively undeveloped domestic markets, and a favorable interest rate environment have made international bonds an attractive financing alternative for many countries. As bonds issued in the international markets are typically denominated in hard currencies, have large volumes and a bullet structure, exposure to exchange rate and refinancing risk has increased. Therefore, risk-mitigating policy actions are needed to prepare for redemption, support debt sustainability, and secure adequate debt management capacity.